Global Imbalances : The Role of Emerging Asia - Pisani, Massimiliano; Cova, Pietro; Rebucci, Alessandro (Washington, D.C. : International Monetary Fund, 2009)
This paper investigates the role played by emerging Asia in the emergence and evolution of the global trade imbalances. Based on simulations in a general equilibrium model of the world economy, we find that a productivity slowdown in the non-tradable sector of these economies in the second half of the 1990s fits regional macroeconomic developments relatively well, but has limited spillover effect to the United States trade balance. In contrast, an increase in the desired level of emerging Asia net foreign assets starting in 2001 not only fits regional developments relatively well, but also has a significant spillover effect to the United States.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet